A Decomposition of the Dual Space of Some Banach Function Spaces - Claudia Capone; Maria Rosaria Formica (Journal of Function Spaces and Applications)
We give a decomposition for the dual space of some Banach Function Spaces as the Zygmund space EXP𝛼 of the exponential integrable functions, the Marcinkiewicz space 𝐿𝑝,∞, and the Grand Lebesgue Space 𝐿𝑝),𝜃.